Central precocious puberty following the diagnosis and treatment of paediatric cancer and central nervous system tumours: presentation and long‐term outcomes. (16th November 2015) - Chemaitilly, Wassim; Merchant, Thomas E.; Li, Zhenghong; Barnes, Nicole; Armstrong, Gregory T.; Ness, Kirsten K.; Pui, Ching‐Hon; Kun, Larry E.; Robison, Leslie L.; Hudson, Melissa M.; Sklar, Charles A.; Gajjar, Amar
Summary: Objectives: To estimate the prevalence of central precocious puberty (CPP) after treatment for tumours and malignancies involving the central nervous system (CNS) and examine repercussions on growth and pubertal outcomes. Design: Retrospective study of patients with tumours near and/or exposed to radiotherapy to the hypothalamus/pituitary axis (HPA). Patients and Measurements: Patients with CPP were evaluated at puberty onset, completion of GnRH agonist treatment (GnRHa) and last follow‐up. Multivariable analysis was used to test associations between tumour location, sex, age at CPP, GnRHa duration and a diagnosis of CPP with final height <‐2SD score (SDS), gonadotropin deficiency (LH/FSHD) and obesity, respectively. Results: Eighty patients (47 females) had CPP and were followed for 11·4 ± 5·0 years (mean ± SD). The prevalence of CPP was 15·2% overall, 29·2% following HPA tumours and 6·6% after radiotherapy for non‐HPA tumours. Height <‐2SDS was more common at the last follow‐up than at the puberty onset (21·4% vs 2·4%, P = 0·005). Obesity was more prevalent at the last follow‐up than at the completion of GnRHa or the puberty onset (37·7%, 22·6% and 20·8%, respectively, P = 0·03). Longer duration of GnRHa was associated with increased odds of final height <‐2SDS (OR = 2·1, 95% CI 1·0–4·3) and longer follow‐up with obesity (OR = 1·3, 95% CI 1·1–1·6). LH/FSHD was diagnosed in 32·6%. There was no independent association between CPP and final height <‐2SDS, and LH/FSHD and obesity in the subset of patients with HPA low‐grade gliomas. Conclusions: Patients with organic CPP experience an incomplete recovery of growth and a high prevalence of LH/FSHD and obesity. Early diagnosis and treatment of CPP may limit further deterioration of final height prospects.